Estimated Ambient Air Pollution Development of the Takalar Industrial Area Using a Box Model - Aulia, Nur; Bintara, Agus; Demmalino, Eymal (Budapest International Research and Critics University, 2021)
Air pollution is the presence of chemicals or other pollutants into the atmosphere that can cause changes to the air composition, so that it deviates normal conditions. Based on data from the Takalar Regency Health Office, ARI (Upper respiratory infection) entered into the category that many people suffered. This study aims to determine air quality by predicting pollutant concentrations based on the types of activities that will be built in industrial estates and the influence of environmental conditions on polluting concentrations. The model box is used to assume the average concentration of pollutants in an area that is devised as a box where the emissions source is spread evenly on the bottom surface of the box. The estimation results showed that from each pollutant there was an increase in concentration from the absence of development projects and with predicted development using the calculation of the box model. The highest concentration increase occurs in TSP pollutants of 5.55%, then NO2 1.03%, SO2 0.19% and the smallest, namely CO of 0.01%. Environmental conditions are very influential on pollutant concentration. Concentration of pollutants is inversely inversely with temperature. When high wind speeds and stable temperatures, the spread of faster pollutants and pollutant concentration does not accumulate around the source of emissions somewhere. The greater the wind speed blows then the polluting concentration will get smaller because it is dispersed in all directions.